About Possibilities to Develop Educational Online Games With the Help Of Web Technologies - Mirabdullayev Ismoiljon Ibrahimjon ugli (Research Parks Publishers, 2021)
This article describes the possibilities of web technology to develop educational online games for young children. It covers the technical possibilities of the virtual games